Assessment of Remineralization Ability of Different Fluoride Varnishes on Artificial Enamel Lesion of Primary Teeth - A Comparative Study - Alazmah Abdulfatah (Wolters Kluwer Medknow Publications, 2024)
AimThe current study's aim was to evaluate the potential of various fluoride varnishes to remineralize artificial enamel lesions on primary teeth. Materials and MethodsFor the study, 90 deciduous molar teeth that were implicated for extraction were taken. A window region with a size of 3 × 3 mm was located in the middle of the tooth's coronal surface. The remaining portion was given a coat of nail polish and given time to dry. A demineralizing solution was used to create the artificial enamel lesion. The samples were randomized into three experimental groups at random, with 30 samples in each group. Group 1: Application of Clinpro White Varnish, Group 2: Application of Duraphat Varnish, and Group 3: Application of MI Varnish. After 14 days, samples from each group were examined under scanning electron microscopy at a magnification of 1000× to determine whether remineralization had occurred. Microhardness was also determined using a microhardness tester. ResultBefore the intervention, the mean demineralized enamel lesion in the Clinpro White Varnish group was 134.44 ± 0.04, in the Duraphat Varnish group was 133.76 ± 0.12, and in the MI Varnish group was 133.89 ± 0.08. After intervention, the maximum remineralized area was found in the MI Varnish group (82.74 ± 0.18) followed by the Clinpro White Varnish group (101.43 ± 0.16) and the Duraphat Varnish group (104.11 ± 0.10). After the intervention, there was a statistically significant difference found between the groups. After the intervention, the maximum microhardness mean value improved in the MI Varnish group (257.03 ± 1.09 to 261.18 ± 1.20) followed by Clinpro White Varnish (258.78 ± 1.64 to 260.10 ± 1.22) and Duraphat Varnish group (255.24 ± 1.51 to 258.02 ± 0.89). ConclusionAccording to the findings of the current investigation, all of the varnishes utilized in this in vitro experiment are capable of correcting early enamel defects on primary teeth. However, MI Varnish group was very effective compared to the Clinpro White Varnish group and the Duraphat Varnish group.